PENGARUH LITERASI EKONOMI TERHADAP PENGELOLAAN UANG SAKU ANAK KELUARGA SUPIR TRUK DI PONTIANAK - Nugroho, Teguh; Witarsa, Witarsa; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to investigate: 1) the level of economic literacy among children from truck driver families in Pontianak, 2) the management of pocket money among children from truck driver families in Pontianak, 3) whether there is a correlation between economic literacy and the management of pocket money among children from truck driver families. A quantitative and causal research approach used in this research. The population under study comprises 110 individuals, with a sample size of 87 respondents, who are truck drivers' children. The research employs random sampling technique for the sample selection. Simple linear regression analysis is used to analyze the data. The research findings indicate: 1) truck drivers children's perspective on economic literacy is included in the high category with a percentage of 79.72%. 2) the management of pocket money for truck driver's children is very high with a percentage of 82.32%. 3) Economic literacy has an influence on the management of pocket money, with the influence of economic literacy on the management of pocket money in truck driver families in Pontianak of 18%. Based on the SPSS 26 calculation, a significance of 0.000 0.05 was obtained, indicating that H0 is rejected and Ha can be accepted. then it can be concluded that is an influence economic literacy on pocket money management for the children of truck driver families in Pontianak.